Effect of hangekobokuto for amelioration of aggressiveness and social behavior in socially isolated mice. Issue 2 (2nd May 2018) - Harada, Yoshinao; Yamaguchi, Takuji; Hu, Ailing; Otani, Satoru; Han, Cheolsun; Kurihara, Yumiko; Kobayashi, Hiroyuki; Arai, Hajime
ABSTRACT: Aim: Hangekobokuto, a kampo medicine, is considered effective against anxiety neurosis, amnesia, insomnia, and neurotic gastritis. The mechanism of action and verification of effect, however, remain to be confirmed. The aim of this study was therefore to confirm the effect of hangekobokuto for amelioration of aggressiveness and social behavior in a mouse stress model. Methods: Four‐week‐old male ddY mice were socially stressed by isolated rearing for 4 weeks. The control group was reared in a social group. Hangekobokuto was then given orally in drinking water to the isolation‐reared mice at a dose of 0% (purified water), 0.25% and 0.5% for 2 weeks. The socially reared control group was not given any treatment. Aggressiveness and social behavior were evaluated. Blood samples were obtained after the test, and serum corticosterone and interleukin (IL)‐6 were measured. The prefrontal region of the brain and the brainstem region were enucleated, and serotonin, dopamine and IL‐6 were measured. Results: Hangekobokuto dose‐dependently controlled the aggressive behavior induced by isolation stress, and the effect disappeared on 5HT1A receptor antagonist treatment. Blood corticosterone, increased by isolation stress, decreased with hangekobokuto treatment. Serotonin and dopamine in the prefrontal region, decreased by isolation stress, increased with hangekobokuto treatment. IL‐6 in the brainstem, increased by isolation stress, decreased dose dependently on hangekobokuto treatment. Conclusion: Hangekobokuto ameliorates aggressiveness induced by anxiety caused by stress. Furthermore, the mechanism of effect involves the serotonin system.